A Variation of the Mardešić Conjecture - Ishiu, Tetsuya (Topology Proceedings, 2024)
We shall show that if d is a positive integer, K_i is a compact linearly ordered topological space for each i<d, Z_j is a nonseparable Hausdorff space for each j<d, and there is a continuous surjection from a countably compact subspace of _i<d K_i onto _j<d Z_j, then every Z_j is a continuous image of a countably compact GO-space. Several variations of this theorem are also proved.